2020
DOI: 10.1021/acs.jpcc.0c02211
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemical Reactions of MoDTC Lubricant Additives with Iron by Quantum Mechanics/Molecular Mechanics Simulations

Abstract: The remarkable lubricant properties of molybdenum dithiocarbamates (MoDTCs) make this class of oil additives well-known in the automotive industry. However, the mechanism of function of these compounds is still not completely understood at the atomistic level. We provide new insights into the dissociation of MoDTCs in tribological conditions, which are the key to describe the debated mechanism to form MoS2. Quantum mechanics/molecular mechanics (QM/MM) dynamic simulations allowed us to monitor in real time the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…We additionally verified what is the most favorable fragmentation pattern for the complexes adsorbed on iron. For this purpose, we optimized the geometry of the fragments of mMoDTC on iron, in analogy to the investigation carried out for the dimeric complex, 30 and we calculated the dissociation energies as where E frag1 Fe and E frag2 Fe are the total energies of the lateral ligands and the central units of mMoDTC adsorbed on iron, respectively. Cuts 1 and 3 were the dissociative patterns considered to generate the molecular fragments adsorbed on iron.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We additionally verified what is the most favorable fragmentation pattern for the complexes adsorbed on iron. For this purpose, we optimized the geometry of the fragments of mMoDTC on iron, in analogy to the investigation carried out for the dimeric complex, 30 and we calculated the dissociation energies as where E frag1 Fe and E frag2 Fe are the total energies of the lateral ligands and the central units of mMoDTC adsorbed on iron, respectively. Cuts 1 and 3 were the dissociative patterns considered to generate the molecular fragments adsorbed on iron.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that this phenomenon also occurs for the dimeric MoDTC structures and complexes with a similar structure. 30 , 34 This phenomenon is due to the capability of the metallic substrate to stabilize more efficiently the fragments originating by separating the complexes between the chalcogen atoms and the carbon atom of the ligand unit. mMoDTC compounds follow the general rules derived for these small organometallic complexes While the fragmentation of isolated complexes is not favorable, the metallic substrate is able to stabilize the molecular fragments and the dissociation energies become favorable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 12 × 12 × 12 K-point grid was used to sample the Brillouin zone of the iridium bulk and the K-point grid was proportionally resized for all the following calculations. We chose not to add any dispersion correction, consistently with our previous investigations [ 56 57 ], because these corrections often overestimate the adsorption energies on metallic substrates [ 58 59 ]. The process of geometry optimization was stopped when the total energy and the forces converged under thresholds of 1 × 10 −4 Ry and 1 × 10 −3 Ry/bohr, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Computational modeling studies of molybdenum additive adsorption chemistry have shown that the presence of oxygen in the additive structure can improve the adsorption of the additive on iron, facilitating the molecular orientation required for MoS 2 formation [61,62]. The lack of oxygen in the sulfur-rich MoDTC trimer may encourage the formation of amorphous molybdenum sulfides, whereas the oxygenated MoDTC dimer and molybdate ester are likely to bind more favorably to the iron surface in order to decompose into well-oriented, crystalline MoS 2 sheets.…”
Section: Discussionmentioning
confidence: 99%